Evaluation of In-Memory Database in Academic Information System with Combination Approach - Haerullah Haerullah (Journal of Creative Power and Ambition (JCPA), 2026)
In the era of modern information systems, improving database efficiency and performance is one of the critical factors to ensure smooth operations and real-time transaction processing. This study aims to evaluate the application of in-memory databases in academic information systems. The research method uses a combination of quantitative and qualitative approaches. The importance of this research lies in the central role of database efficiency in supporting the performance, speed of service, and reliability of academic information systems. The analysis was performed using the TPC-C benchmark scenario to compare the performance between disk-based and in-memory databases under various test conditions. The results show that the use of in-memory databases provides faster response times and higher transaction throughput compared to disk-based databases, especially in online transaction processing (OLTP) transactions. In addition, the test results also highlight the importance of index optimization strategies and parallelism settings in supporting system performance. This study provides strategic recommendations related to the migration of academic information systems to in-memory architecture to improve overall operational efficiency.